Evaluasi Suplementasi Probiotik dan Asam Organik dalam Air Minum Ayam Petelur di Mega Farm Sukabumi: Evaluation of Probiotic and Organic Acid Supplementation on Drinking Water for Laying Hens at Mega Farm Sukabumi - Havif Zamarath Varhan; S Sumiati; D A Astuti (Jurnal Ilmu Nutrisi dan Teknologi Pakan (Nutrition and Feed Technology Journal), 2022)
There are various studies on AGP substitute feed additives that provide many options for solutions related to the problem of maintaining gut health. Therefore, it is necessary for a fundamental evaluation of the use of some feed additives on the response of livestock. The purpose of this engineering practice is to find best solution for growth promoter antibiotics (AGP) alternatives that can be effectively used in laying hens Farm. Trials of several probiotic and organic acid product supplementation were carried out on 21,000 laying hens of the HyLine Brown strain aged 50 weeks for 1 month. Tested products were protected probiotic powder (OGC), liquid probiotics (PBL) and liquid organic acids (APK), these products were evaluated based on production egg quality and cost feasibility studies. Data on egg production and egg quality were analyzed using ANOVA and then actually compared between treatments with Tukey's test (p<0.05) and also compared based on production standards from producers/breeders. The trial results showed that the use of liquid probiotics (PBL) resulted in the highest egg production and egg weight, organic acid products (APK) resulted in higher distribution of large eggs and more efficient feed conversion, the use of protected probiotic powder (OGC) resulted in highest haugh unit. The economic feasibility study shows that organic acid products (APK) produce the highest return on investment value. The concluded showed that organic acid product (APK) will be effectively used in laying hens Farm. Key words: egg quality, laying hen, organic acid, probiotic